Pengaruh Pendapatan Asli Daerah dan Dana ZIS Terhadap Kemiskinan: Bukti Empiris Data Panel di Aceh - Istafan Najmi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2019)
This study aims to determine the effect of Regional Original Income (PAD), Zakat Infaq and Sadaqah funds (ZIS) on Poverty (MIS) in 23 districts/cities in Aceh province for 5 (five) years, namely 2013-2017. The method used is panel data regression analysis. The Hausman test results (Hausman test) show that the best model for this panel data is a random effect model. This study concludes that the independent variables are simultaneously significant towards poverty. Partially the PAD is significantly negative for the consequences in districts/cities in Aceh province. And ZIS funds are significantly negative towards poverty, meaning that local revenue and zakat infaq and sadaqah funds can reduce poverty in districts / cities in Aceh province. From these findings, it can be interpreted that the ability of independent variables can explain, 95.59% of poverty. And the remaining 4.41% is explained by other variables not included in this study. The district/city government is expected to be able to increase regional original income and infaq and sadaqah zakat funds so that it will continue to contribute to reducing poverty.